Arterial Occlusion After Hyaluronic Acid Injection: Treatment With Hyaluronidase and Streptokinase. Issue 6 (December 2021) - Hurkal, Ozgur; Sibar, Serhat; Cenetoglu, Seyhan; Tuncer, Serhan; Elmas, Cigdem; Seymen, Cemile Merve
Abstract : Abstract: The most feared complication of the hyaluronic acid injections in the periorbital region is embolism of the central retinal artery. The present study aimed to compare the effectiveness of hyaluronidase administered intravenously (systemically) alone or in combination with streptokinase with that of intra-arterial revascularization. Thirty rats were divided into 5 groups. The bilateral oblique groin flap of the rats was raised; the right side was the experiment group, and the left side was the sham control. The right superficial epigastric artery was occluded with a hyaluronic acid injection. After occlusion, no additional procedures were performed in group 1, whereas group 2 received systemic hyaluronidase, group 3 received intra-arterial hyaluronidase, group 4 received systemic hyaluronidase and streptokinase, and group 5 received intra-arterial hyaluronidase and streptokinase. On the seventh day, the rats were killed, flap necrosis rate was calculated, and histological examination was performed. There was no significant difference in the necrosis rates of the rats in groups 2, 3, 4, and 5 ( P > 0.05). In histological evaluation, the histological view closest to normal arterial structure was observed in group 4. Immunohistochemical analysis revealed that the ischemia scores of systemic therapy were significantly lower than those of intra-arterial therapy. These results have shown that hyaluronidase and streptokinase administered systemically is as effective as intra-arterial revascularization and does not cause arterial wall degeneration. It has been shown that systemic administration of hyaluronidase and streptokinase is as successful as intra-arterial revascularization in the treatment of arterial embolism with hyaluronic acid.